Empowering Women’s Health: Transforming Maternal Health Care in India - Gomathi Ananda Kumar; Veeramani Palaniyappan (Journal Of Social Science (JoSS), 2023)
An indicator of the reproductive health of women in an area is the maternal mortality rate. A lot of women in the reproductive age range pass away from difficulties during, during, or related to pregnancy, childbirth, or abortion. Maternal mortality, a critical indicator of a country's healthcare system and women's well-being, has been a persistent concern in India. The study examines the progress and strategies employed in reducing maternal mortality in India. The research explores the initiatives undertaken by the Indian government under the National Health Mission to address maternal health. The findings serve as a valuable resource for policymakers, healthcare professionals, and researchers striving to advance women's sexual and reproductive health rights while reducing maternal mortality globally. KEYWORDS: Maternal mortality, Reproductive health, women, India